2008
DOI: 10.1002/ejsp.572
|View full text |Cite
|
Sign up to set email alerts
|

When words feel right: How affective expressions of listeners change a speaker's language use

Abstract: Based on conversation research and work showing that affective cues help to tune information processing to situational demands, it was hypothesized that affective expressions of listeners would influence how speakers represent communicated information in language. Participants were asked to orally communicate an event presented in a film clip to two other participants. These other participants were actually confederates who either adopted a positive or negative nonverbal expression during the story of the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 40 publications
0
26
0
1
Order By: Relevance
“…Because affective expression goes beyond our basic wants and needs, it is considered higher order language. Beukeboom suggests that affective expression changes the direction and course of a conversation [60]. For example, if one speaker is not receiving the affective expressions they expect or desire, that speak may in turn change the path of conversation from what they were originally trying to express.…”
Section: Social Context Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…Because affective expression goes beyond our basic wants and needs, it is considered higher order language. Beukeboom suggests that affective expression changes the direction and course of a conversation [60]. For example, if one speaker is not receiving the affective expressions they expect or desire, that speak may in turn change the path of conversation from what they were originally trying to express.…”
Section: Social Context Appraisalmentioning
confidence: 99%
“…For example, if one speaker is not receiving the affective expressions they expect or desire, that speak may in turn change the path of conversation from what they were originally trying to express. Affective expression allows for adaptability and flexibility [60]. Individuals with HFA and PLI may have difficulty with affective expression, which ultimately may impact the quality and strength of a relationship with a peer, friend, teacher, or family member.…”
Section: Social Context Appraisalmentioning
confidence: 99%
“…For example, students who have difficulties with affective expression may not be able to appropriately maintain a topic, change the topic, transition, or close a conversation. A study conducted by Beukeboom explored affective expression in conversation and found that the perception and use of expressions may change the course of a conversation [40]. For example, if the speaker is not receiving the affective expressions they are looking for from the listener, the speaker may change their use of language and in-turn, what they were originally trying to convey [40].…”
Section: Open Access Freely Available Onlinementioning
confidence: 99%
“…A study conducted by Beukeboom explored affective expression in conversation and found that the perception and use of expressions may change the course of a conversation [40]. For example, if the speaker is not receiving the affective expressions they are looking for from the listener, the speaker may change their use of language and in-turn, what they were originally trying to convey [40]. The correct use of affective expression allows for both conversational partners to be flexible during conversation and appropriately adapt to their partners' comments [40].…”
Section: Open Access Freely Available Onlinementioning
confidence: 99%
“…The previously mentioned work of Beukeboom andSemin (2005, 2006) argues that if affective cues tune the level of abstraction in which people cognitively deal with information, then this should be reflected in the language that people use, specifically in language abstraction. Several experiments provided empirical evidence for this idea.…”
Section: Feelings and Language Usementioning
confidence: 99%